Dynamical masses of early-type galaxies at z ∼ 2: Are they truly superdense? - Cappellari, M; Di Serego Alighieri, S; Cimatti, A; Daddi, E; Renzini, A; Kurk, J; Cassata, P; Dickinson, M; Franceschini, A; Mignoli, M; Pozzetti, L; Rodighiero, G; et al. (Institute of Physics Publishing, 2009)
We measured stellar velocity dispersions σ and derived dynamical masses of nine massive (M ≈ 1011 M ⊙) early-type galaxies (ETGs) from the Galaxy Mass Assembly ultra-deep Spectroscopic Survey (GMASS) sample at redshift 1.4 ≲ z ≲ 2.0. The σ are based on individual spectra for two galaxies at z ≈ 1.4 and on a stacked spectrum for seven galaxies with 1.6 < z < 2.0, with 202 hr of exposure at the ESO Very Large Telescope. We constructed detailed axisymmetric dynamical models for the objects, based on the Jeans equations, taking the observed surface brightness (from deep HST/ACS observations), point-spread function, and slit effects into account. Our dynamical masses M Jeans agree within ≲30% with virial estimates M vir = 5 × Reσ2/ G, although the latter tend to be smaller. Our M Jeans also agrees within a factor ≲2 with the M pop previously derived using stellar population models and 11 bands photometry. This confirms that the galaxies are intrinsically massive. The inferred mass-to-light ratios (M/L) U in the very age-sensitive rest-frame U band are consistent with passive evolution in the past 1 Gyr (formation redshift zf ∼3). A "bottom-light" stellar initial mass function appears to be required to ensure close agreement between M Jeans and M pop at z ∼2, as it does at z ∼0. The GMASS ETGs are on average more dense than their local counterpart. However, a few percent of local ETGs of similar dynamical masses also have comparable σ and mass surface density Σ50 inside R e. © 2009. The American Astronomical Society. All rights reserved.